Life of the Chepang now and then: A Study of Chitwan District - Adhikari, Rishiram (Nepal Journal of Multidisciplinary Research, 2023)
The Chepang is one of the indigenous nationalities of Nepal have changed their life style in short span of time. The study analyzes changing aspects of the Chepang in term of socio cultural, religious and economic pattern. Main objective of this study is to examine why and how the life pattern of the Chepang has been changed in Chitwan in short span of time. Qualitative research design has been followed to analyze the changing socio –economic, cultural religious status of the Cheapng. Both primary and secondary source of data were used for this study and conclusion of the study is based on the collected information. It is found that life of the Chepang have been changed due to modernization, Christianization, invasion of neighboring culture and political system of the nation.